1989
DOI: 10.1002/ajp.1350180102
|View full text |Cite
|
Sign up to set email alerts
|

Styles of dominance and their endocrine correlates among wild olive baboons (Papio anubis)

Abstract: We have studied the relationship between dominance rank and physiology among male olive baboons (Papio anubis) living freely in a national park in Africa. In stable hierarchies, dominant males consistently have lower basal concentrations than do subordinates of the adrenal glucocorticoid cortisol. Because of the known catabolic actions of glucocorticoids, dominant males may be less at risk for some of the pathogenic consequences of glucocorticoid overexposure. We find that low basal cortisol concentration is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(97 citation statements)
references
References 26 publications
3
93
0
1
Order By: Relevance
“…Another subset of subordinate males, who initiate fights or displace aggression afterwards, have relatively low cortisol concentrations [25]. Together, these studies suggest that olive baboons exhibit a variety of behavioral styles and coping strategies and that these behavioral traits may impact both social rank and cortisol concentrations [20,25,34]. Dominant African wild dogs (Lycaon pictus) also tend to exhibit dimorphic behavioral and endocrine patterns in captivity [35].…”
Section: Behavioral Strategiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Another subset of subordinate males, who initiate fights or displace aggression afterwards, have relatively low cortisol concentrations [25]. Together, these studies suggest that olive baboons exhibit a variety of behavioral styles and coping strategies and that these behavioral traits may impact both social rank and cortisol concentrations [20,25,34]. Dominant African wild dogs (Lycaon pictus) also tend to exhibit dimorphic behavioral and endocrine patterns in captivity [35].…”
Section: Behavioral Strategiesmentioning
confidence: 96%
“…Likewise, this second subpopulation of dominant animals frequently uses outlets for frustration (for example, displacement of aggression on lower ranking individuals). The authors of the study suggest that rather than being a marker for dominance, low baseline cortisol concentrations are more closely correlated with behavioral traits that may affect outcome of a dominance interaction [34]. There also appears to be subpopulations of subordinate males with behavioral and physiological characteristics that differ from the typical subordinate population values [25].…”
Section: Behavioral Strategiesmentioning
confidence: 97%
See 1 more Smart Citation
“…What does the experience of power correlate with in the phenomenological moment? Studies seeking answers to this question have found that contextual shifts in the individual's power lead to, for example, variation in cortisol (Ray & Sapolsky, 1992;Sapolsky & Ray, 1989) and testosterone (Bernhardt, 1997;Dabbs, 1997;Gladue, Boechler, & McCaul, 1989;Mazur & Booth, 1998), linguistic and paralinguistic behavior (Dovidio & Ellyson, 1982;Hall, Coats, & LeBeau, 2005;Tiedens & Fragale, 2003), as well as strategic social behavior and mood (Moskowitz, 1994).…”
Section: Traditions In the Empirical Study Of Powermentioning
confidence: 99%
“…It seems likely that differences in recent experience (e.g. defeat in male-male interactions depresses testosterone levels, Raleigh and Macquire, 1990;Rose et al, 1975;Sapolsky, 1987), or in personality (Sapolsky and Ray, 1989), may be more important than small differences in body size when males decide whether or not to attempt a dominance take-over.…”
Section: What Makes a Successful Male Mandrill?mentioning
confidence: 99%